Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store

Solve the following equation having given log2, log3 and log7,
${21^x} = {2^{2x + 1}}{.5^x}$

seo-qna
Last updated date: 20th Jun 2024
Total views: 405k
Views today: 10.05k
Answer
VerifiedVerified
405k+ views
Hint: To solve this question, we will use some of the logarithmic properties, i.e. $\log {a^b} = b\log a,\log \left( {ab} \right) = \log a + \log b$ etc. using these properties, we can solve this.

Complete step-by-step answer:
We have,
${21^x} = {2^{2x + 1}}{.5^x}$ …… (i)
Taking log both sides,
$ \Rightarrow \log \left( {{{21}^x}} \right) = \log \left( {{2^{2x + 1}}{{.5}^x}} \right)$
We know that,
$ \Rightarrow \log {a^b} = b\log a$ and $\log \left( {ab} \right) = \log a + \log b$
So,
$ \Rightarrow x\log \left( {21} \right) = \log \left( {{2^{2x + 1}}} \right) + \log \left( {{5^x}} \right)$
$ \Rightarrow x\log \left( {21} \right) = \left( {2x + 1} \right)\log \left( 2 \right) + x\log \left( 5 \right)$
We can also write this as,
$ \Rightarrow x\log \left( {7.3} \right) = \left( {2x + 1} \right)\log \left( 2 \right) + x\log \left( 5 \right)$
It will become,
$ \Rightarrow x\log \left( 7 \right) + x\log \left( 3 \right) = \left( {2x} \right)\log \left( 2 \right) + \log \left( 2 \right) + x\log \left( 5 \right)$
Separating the coefficients of x,
$ \Rightarrow x\left[ {\log \left( 7 \right) + \log \left( 3 \right) - 2\log \left( 2 \right) - \log \left( 5 \right)} \right] = \log \left( 2 \right)$
$ \Rightarrow x = \dfrac{{\log \left( 2 \right)}}{{\left[ {\log \left( 7 \right) + \log \left( 3 \right) - 2\log \left( 2 \right) - \log \left( 5 \right)} \right]}}$ …….. (ii)
As we know that, log10 =1
We can write log10 as:
$ \Rightarrow \log \left( {5.2} \right) = 1$
$ \Rightarrow \log \left( 5 \right) + \log \left( 2 \right) = 1$
$ \Rightarrow \log \left( 5 \right) = 1 - \log \left( 2 \right)$
Putting this value in equation (ii),
$ \Rightarrow x = \dfrac{{\log \left( 2 \right)}}{{\left[ {\log \left( 7 \right) + \log \left( 3 \right) - 2\log \left( 2 \right) - 1 + \log \left( 2 \right)} \right]}}$
$ \Rightarrow x = \dfrac{{\log \left( 2 \right)}}{{\left[ {\log \left( 7 \right) + \log \left( 3 \right) - \log \left( 2 \right) - 1} \right]}}$
Here, we can see that the value of x is in the form having the given log2, log3 and log7.
Hence, it is the correct answer.

Note: Y times the logarithm of x is the logarithm of the exponent x, elevated to the power of y. The power rule can be used by multiplication operation for quick exponent calculation. Where appropriate, use the correct formula or logarithm and try to solve the problem.